More networks, more financial inclusion? An empirical evidence from Indonesia - Pertiwi, Ristiyanti Hayu; Muzayanah, Irfani Fithria Ummul (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2022)
Social capital is essential in mediating financial inclusion. We employ broader horizontal and vertical social engagement of social capital such as bonding, bridging and linking. Meanwhile, financial inclusion is defined as saving ownership in a formal financial institution. Using a logistic regression model and a sample of 74,454 individual respondents from the 2018 National Socioeconomic Survey, we found that social capital is essential in promoting formal saving behavior. Among three indicators (bonding, bridging, and linking), the results show that a rise in the bridging variable was associated with a 10 per cent higher likelihood of having a formal savings, higher in magnitude than the linking variable. Bonding variable had no effect in promoting financial inclusion, but upon further observation, it was still suitable to be implemented in rural area. Our estimates justified the presence of financial information transmission among people in their respective social circles. Our findings suggest that the government should consider a financial campaign using a community-based approach to complement the current inclusion strategy.JEL Classification:  D14; G41; O17